FPGA Implementation of a PV Generator and a Boost Converter Controllers for a Virtual Laboratory Environment - Bautista, Oscar; Bernal, Álvaro; Pantoja, Andrés; Revelo, Javier (Iranian journal of science and technology. Transactions of electrical engineering, 2024)
This paper presents an FPGA hardware implementation of two different components of a microgrid’s electrical systems. Small and isolated microgrids are currently a frequent solution for electricity coverage in remote areas, where detailed studies, simulations, and realistic emulations are required to design appropriate systems according to each location. Hardware implementations based on a Labview environment of 240 W and 330 W generic photovoltaic generators, a Boost converter, and P &O algorithm were performed. The results obtained from the panels and converter were compared to the Simulink response. Unified systems, with and without controls, were compared. The systems were first compiled individually on an FPGA NI PCIe 7841R and later unified. The data and performance obtained from the emulated environment were verified using Simulink models, and the desired correspondence was obtained.